Pengaruh Tingkat Profitabilitas Terhadap CSR (Studi Empiris Perusahaan Manufaktur Sektor Semen, Keramik, Porselen Dan Kaca Yang Terdaftar Di BEI Tahun 2018-2020) - Yefta Andi Kus Noegroho; Adriana Sipora Saefatu (Politeknik Ganesha Medan, 2022)
This study was conducted with the aim of knowing whether there is an influence on the profitability of manufacturing companies in the cement, ceramic, porcelain, and glass sectors listed on the Indonesia Stock Exchange in 2018-2020 on Corporate Social Responsibility. The company's profitability can be affected by circumstances such as the Covid-19 pandemic because it disrupts the company's operations so that many companies experience a decline in profits during the pandemic. Profitability measurement is carried out using financial ratios, namely Net Profit Margin (NPM), while Corporate Social Responsibility is measured using the Corporate Social Responsibility Disclosure Index (CSRDI). This study uses 35 samples of cement, ceramic, porcelain, and glass manufacturing companies listed on the IDX from 2018 to 2020 where the type of data used is secondary data obtained from the company's financial statements. The test for this hypothesis is multiple linear regression using SPSS version 22. The results show that profitability has a positive effect on Corporate Social Responsibility. In addition to profitability, there is also the size of the company which has a positive influence on Corporate Social Responsibility.